Sosialisasi Kesehatan pada Masyarakat di Desa Selekan, Kecamatan Liang, Kabupaten Banggai Kepulauan: Health Socialization to the Community in Selekan Village, Liang District, Banggai Islands Regency - Putri Ana Tasya; Caca Sudarsa; Rini Inriani; Husnul Fatima Olii; Eva Febriani Saleng; Shusmufidha; Melsa Megayanti; Ni Komang Julianti; Paramita Bana; Putri Sobbay; Frengky Dalani; Moh Fauzan (Jurnal Pengabdian MALEO, 2022)
Pengalaman Belajar Lapangan (PBL) 1 pada Fakultas Kesehatan Masyarakat (FKM) adalah proses belajar untuk mendapatkan kemampuan profesional kesehatan masyarakat. Penelitian ini bertujuan untuk memperoleh gambaran tentang pengetahuan,sikap dan tindakan masyarakat terhadap masalah kesehatan yang ada di Desa Selekan. Penelitian ini bersifat deskriftif dengan pendekatan kuantitatif, Populasi dalam penelitian ini adalah seluruh Rumah Warga yang ada di Desa Selekan Dusun I, Dusun II dan Dusun III. Sampel dalam penelitian ini dihitung menggunakan aplikasi SPSS dengan jumlah sampel 544. Data dikumpulkan dengan menggunakan kuisioner dan diolah secara komputerisasi dan disajikan dalam bentuk tabel distribusi frekwensi. Hasil pretest program intervensi pemilahan sampah, penanganan akhir sampah, vektor pembawa penyakit (lalat), penyakit menular DBD, penyakit tidak menular gastritis, gula darah, pentingnya mengkonsumsi buah, stunting, kepemilikan kartu JKN, bahaya merokok menunjukkan bahwa pengetahuan Responden masih dalam kategori cukup, sedangkan sikap dan tindakan masyarakat sudah baik. Kesimpulan mahasiswa PBL 1 posko desa selekan melakukan 10 program intervensi. Saran petugas kesehatan perlu melakukan sosialisasi penyuluhan tentang pencegahan penyakit. Waste management is still a serious problem in Selekan Village, one of which is the lack of garbage disposal facilities. It's the same as the problem of infectious diseases DHF and non-communicable diseases Gastritis which both occupy the position of disease with the first highest sufferer in Selekan Village. People's habits of consuming fruit every day, checking blood sugar regularly, and public awareness about the dangers of smoking are still low. Smoking habits are very difficult to leave because cigarettes contain nicotine which is addictive for the body. Although the addictive content of cigarettes is not as heavy as addictive in narcotics, the addictive substance of cigarettes is very difficult to release. The problem of disease-carrying vectors (flies) which could be due to a lack of public awareness in processing waste. Ownership of a JKN card is also still a problem that needs to be resolved in Selekan Village. The implementation of JKN in Indonesia faces various challenges, in terms of service quality, providing quality health services, as well as the JKN program. This type of activity uses descriptive research methods, then data is collected using questionnaires and processed computerized and presented in the form of a frequency distribution table. The results of the pre-test of the waste sorting intervention program, final handling of waste, disease-carrying vectors (flies), infectious diseases of dengue fever, non-communicable disease gastritis, blood sugar, the importance of consuming fruit every day, stunting, JKN card ownership and the dangers of smoking indicate that respondents' knowledge is still low. in the sufficient category, while the attitudes and actions of the community are in the good category. Local health workers need to work together with the Selekan Village government to disseminate information on diseases and PHBS to all Selekan Village communities to increase community knowledge, attitudes and actions, especially in the field of individual and group health.